2017
DOI: 10.1002/mc.22764
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: LncAPC drives Wnt/β‐catenin activation and liver TIC self‐renewal through EZH2 mediated APC transcriptional inhibition

Abstract: Liver tumor initiating cells (TICs), a small subset cells in tumor bulk, are responsible for liver tumor initiation, metastasis, and relapse. However, the regulatory mechanism of liver TICs remains largely unknown. Here we found a long noncoding RNA lncAPC, locating near from APC locus, was highly expressed in liver cancer and liver TICs. LncAPC was required for liver TIC self-renewal. Silencing and overexpressing lncAPC showed impaired and enhanced sphere formation capacity of liver TICs, respectively. By rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 42 publications
1
16
0
Order By: Relevance
“…Although CDH1 is a well-known repressed gene by EZH2 [29,30], our study suggested, for the first time, that numerous additional genes were also controlled by EZH2 and KDM6B during EMT. Interestingly, it has been previously reported in liver cancers that EZH2 repressed, in an H3K27me3-dependent manner, the APC promoter leading to the activation of the Wnt/β-Catenin pathway [31]. Interestingly, our study confirmed the presence of both EZH2 and the H3K27me3 mark on the APC promoter (data not shown) demonstrating the validity of our model and experimental scheme.…”
Section: Discussionsupporting
confidence: 84%
“…Although CDH1 is a well-known repressed gene by EZH2 [29,30], our study suggested, for the first time, that numerous additional genes were also controlled by EZH2 and KDM6B during EMT. Interestingly, it has been previously reported in liver cancers that EZH2 repressed, in an H3K27me3-dependent manner, the APC promoter leading to the activation of the Wnt/β-Catenin pathway [31]. Interestingly, our study confirmed the presence of both EZH2 and the H3K27me3 mark on the APC promoter (data not shown) demonstrating the validity of our model and experimental scheme.…”
Section: Discussionsupporting
confidence: 84%
“…In our experiment, transcriptome analysis after LIPUS stimulation revealed significant differences in 27 genes, with 15 genes up-regulated and 12 down-regulated. Among them, KMT2A, APC, DYRK1A, and other genes that played an important role in transcriptional activation 45 , 46 , cell adhesion 47 , and regulation of cell proliferation signals, were up-regulated 48 . Meanwhile, WFS1 and other genes that participated in the occurrence and development of a variety of diseases, were down-regulated 49 .…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, lncAPC inhibits transcription of APC via recruiting EZH2 to be a APC promoter, which facilitates the activation of Wnt/β-catenin signaling and liver TIC self-renewal [24] ( Figure 1C). Overexpression of lncWDR26 (GenBank Accession no.…”
Section: Transcriptional Regulationmentioning
confidence: 99%